Polymorphism and Association of 5’UTR CAPN1 Gene with Growth Traits in Bali Cattle by PCR-RFLP - D. E. W. T. Sihite; R. Priyanto; Jakaria Jakaria (Faculty of Animal Science, Bogor Agricultural University, 2019)
The aim of this study was to identify the variation of 5’UTR CAPN1 gene and its association to growth traits in Bali cattle. DNA samples were obtained from 80 heads of Bali cattle originated from BPTU-HPT Denpasar. The average of Bali cattle age was 784 days (631 days-1098 days). Bali cattle were divided into 3 age groups namely, the first group (1.5 years to 2 years), the second group (2 years to 2.5 years), and the third group (2.5 years to 3 years). The observed growth traits were birth weight (kg), live weights (kg), average daily gain (kg), body length (cm), chest depth (cm), withers height (cm), hip height (cm), and heart girth (cm). Polymorphism identification of 5’UTR CAPN1 gene was conducted by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) with BglII as the restriction enzyme. Growth traits data association were analyzed using the General Linear Model (GLM) analysis. The 5’UTR CAPN1 gene|BglII was polymorphic in Bali cattle (GG, GT, and TT). Genotype frequencies for Bali cattle were 0.30 (GG), 0.66 (GT), and 0.04 (TT). The allele frequencies of G and T allele were 0.63 and 0.37, respectively. The G allele was the most frequent allele and GT genotype was the most frequent genotype among the cattle. The CAPN1|BglII had a significant effect (p<0.05) on growth traits in Bali cattle. Animal carrier of GG genotype had higher live weight and average daily gain than those with GT genotype, while the lowest values were associated with TT genotype.